MODELLING THE BEHAVIOUR OF HOMOGENEOUS EXPLOSION IN A CLOSED VESSEL WITH THREE-STEP REACTION MODEL (FUDMA JOURNAL OF SCIENCES, 2023)
This study presents numerical simulations of a spatially homogeneous explosion in a closed vessel having thermal and chain-branching reaction models. The simulations are performed using three-step models of chemical kinetics. A fourth-order Runge-Kutta method was used to carry out the simulations. The result of the study revealed that when values of crossover temperature, , is sufficiently less than unity, the homogeneous explosion is described by the purely three-step chain-branching reaction model. While for  greater than unity, the homogeneous explosion exhibits a considerable thermal explosion structure. This indicates that the crossover temperature influence the nature of explosion and hence determines the exothermicity of the reaction (thermal explosion) or its chain character (branched-chain explosion). For more exploration, there may be need to extend to an asymptotic method. For further study, it was suggested that higher values of activation energy  and the crossover temperature  may be investigated.
Keywords: Homogeneous Explosion, Crossover Temperature, Closed Vessel, Three-step Reaction Model